The Effect of Independent Humidity Control on Aerosol Drug Delivery During Adult Invasive Mechanical Ventilation. - Zhang, Madeline X.; Huijgen, Tom; Öhrneman, Hugo; Bonn, Daniel; van Rijn, Cees J.M.; Löndahl, Jakob (Respiratory Care, 2026)
Background: Aerosol therapy is commonly performed during invasive mechanical ventilation. Although heated humidification is standard practice, studies suggest that humidity can reduce the delivered dose. In this study, we aimed to investigate whether the delivered dose can be increased by decoupling humidity control from heating during aerosol drug delivery. Methods: In a bench study setup, albuterol sulfate solution was nebulized into an adult invasive mechanical ventilation circuit with a vibrating-mesh nebulizer. An absolute humidifier with decoupled heating and humidification was tested at 0 and 25 mg H2O/L of added humidity during nebulization and compared with 2 conventional pass-over humidifiers with no independent humidity control. The delivered dose, experimentally determined by the drug deposition on a filter between the endotracheal tube and the test lung, was quantified with a UV–Vis spectrometer. The particle size distribution of the aerosol entering the test lung was measured and used to model the lung deposited dose for healthy and diseased lungs. Results: The absolute humidifier at 0 mg/L added humidity led to a significantly higher delivered dose (37.2%) than the pass-over humidifiers (21.2% and 24.1%, P =.01 for both), whereas the absolute humidifier at 25 mg H2O/L added humidity led to a comparable dose (24.9%) as one of the pass-over humidifiers. All these test scenarios achieved sufficient humidity (>33 mg H2O/L) in the gas flow during nebulization. Regional lung deposition simulations suggest that <10% of the nebulized dose deposits in healthy lungs for the pass-over humidifiers and around 16% for the absolute humidifier at 0 mg/L added humidity. Simulations also suggest that bronchial obstruction increases the deposited dose, whereas alveolar enlargement decreases the deposited dose. Conclusions: The delivered dose and hence the simulated lung deposited dose was improved by allowing independent humidity control during nebulization for adult invasive mechanical ventilation.